ExtraLevatory AbdominoPerineal Excision (ELAPE) Does Not Result in Reduced Rate of Tumor Perforation or Rate of Positive Circumferential Resection Margin: A Nationwide Database Study. Issue 5 (May 2015) - Klein, Mads; Fischer, Anders; Rosenberg, Jacob; Gögenur, Ismail
Abstract : Objective: To evaluate the oncological results and possible benefits associated with e xtra l evatory a bdomino p erineal e xcision (ELAPE) when compared with conventional abdominoperineal excision (APE). Background: ELAPE was introduced in 2007 with the purpose of reducing the rate of positive resection margins after resection of low rectal cancers. Preliminary studies have shown promising results. No large-scale or nationwide data have been presented. Methods: Database study based on data from the Danish Colorectal Cancer Group's prospective database. Data on all ELAPEs and APEs performed in Denmark in the period January 1, 2009, through August 2012 were retrieved and evaluated for differences in demography, tumor characteristics, and oncological results. Uni- and multivariate logistic regression analyses were performed to identify risk factors for resection with a positive circumferential resection margin (CRM+). Results: A total of 554 patients were included, 301(54%) were operated by ELAPE; 253(46%) by APE. Sixty-three percent were men, median (interquartile range) age was 69 (61–76 years) years, and tumors removed had predominantly T-stages T2 and T3 (32% and 45%, respectively). Overall, CRM+ was found in 13% of patients. When divided according to type of procedure, we found no significant differences in demography and tumor T- and N-stages. Resections with a CRM+ were more common after ELAPE (16% vs 7%; P = 0.006). After uni- and multivariate logistic regression analyses, surgery by ELAPE remained a risk factor for a CRM+ [odds ratio, 2.59 (95% confidence interval, 1.31–5.12); P = 0.006). Conclusions: In this nationwide study, resection of low rectal cancers by ELAPE did not improve short-term oncological results, when compared with conventional APE. Abstract : Nationwide database study comparing oncological results after conventional abdominoperineal excisions versus extralevatory abdominoperineal excisions performed in Denmark 2009 through August 2012. In contrast to previous studies, no oncological benefits are found with the extralevatory approach. On the contrary, there was an increased risk of circumferential resection margin involvement associated with ExtraLevatory AbdominoPerineal Excision.